PENGARUH PENGGUNAAN METODE BERNYANYI TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN ILMU PENGETAHUAN ALAM DAN SOSIAL KELAS V DI SDN 39 SEJIRAM TAHUN PELAJARAN 2024/2025 - Iin Putri Andini; Parni; Ahmad Rathomi (CV. ADIBA AISHA AMIRA, 2026)
This journal discusses the Effect of Singing Methods on the Learning Outcomes of Fifth-Grade Students at SDN 39 Sejiram in the 2024/2025 Academic Year. This study employs a quantitative approach, specifically an experimental design. This study employed a One-Group Pretest-Posttest Design. Data collection techniques included tests, observations, and documentation. The data analysis technique used was the t-test. The results of this study indicate that: The learning outcomes achieved by students before using the singing method in the 5th-grade IPAS subject at SDN 39 Sejiram had an average of 45.83; The learning outcomes achieved by students after using the singing method in the 5th-grade IPAS subject at SDN 39 Sejiram had an average of 71.17; There is a significant effect of the singing method on students’ learning outcomes in the 5th-grade IPAS subject at SDN 39 Sejiram. This is evidenced by a t-value of -10.079 with a Sig. (2-tailed) value of 0.000 < 0.05, meaning that Ha is accepted and Ho is rejected. This indicates that there is a significant effect of the singing method on student learning outcomes in the 5th-grade IPAS subject at SDN 39 Sejiram, specifically an effect size of 25.34.